2015
DOI: 10.3389/fpsyg.2015.01041
|View full text |Cite
|
Sign up to set email alerts
|

Duration estimates within a modality are integrated sub-optimally

Abstract: Perceived duration can be influenced by various properties of sensory stimuli. For example, visual stimuli of higher temporal frequency are perceived to last longer than those of lower temporal frequency. How does the brain form a representation of duration when each of two simultaneously presented stimuli influences perceived duration in different way? To answer this question, we investigated the perceived duration of a pair of dynamic visual stimuli of different temporal frequencies in comparison to that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
(97 reference statements)
1
7
0
Order By: Relevance
“…Third, performance was better in 1-2-3-Go condition in which subjects made two measurements, as evidenced by a lower root-mean-square error (RMSE) in 1-2-3-Go compared to 1-2-Go condition ( Fig 2C; permutation test; p-value < 0.01 for all subjects). This observation indicates that subjects combined the two measurements to improve their estimates, corroborating reports from other behavioral paradigms [46][47][48][49][50][51][52][53][54]. Combined with the systematic bias toward the mean of t s , these results indicated that subjects integrated prior information with one or two measurements to improve their performance.…”
Section: Subjects Integrate Interval Measurements With Prior Knowledgesupporting
confidence: 85%
See 1 more Smart Citation
“…Third, performance was better in 1-2-3-Go condition in which subjects made two measurements, as evidenced by a lower root-mean-square error (RMSE) in 1-2-3-Go compared to 1-2-Go condition ( Fig 2C; permutation test; p-value < 0.01 for all subjects). This observation indicates that subjects combined the two measurements to improve their estimates, corroborating reports from other behavioral paradigms [46][47][48][49][50][51][52][53][54]. Combined with the systematic bias toward the mean of t s , these results indicated that subjects integrated prior information with one or two measurements to improve their performance.…”
Section: Subjects Integrate Interval Measurements With Prior Knowledgesupporting
confidence: 85%
“…However, since priors and the cost functions impact both 1-2-Go and 1-2-3-Go conditions, moderate inaccuracies in modeling these components may not be able to explain optimal behavior in 1-2-Go and suboptimal behavior in the 1-2-3-Go condition simultaneously. Finally, recent results suggest the performance may be limited by imperfect integration [70,71] and imperfect memory [48,72], which future models of sequential updating should incorporate.…”
Section: /34mentioning
confidence: 99%
“…The optimal integration of multiple sensory signals predicts an improvement in timing sensitivity. However, this prediction has not been confirmed experimentally in some studies 21 , 27 . Hartcher-O’Brien et al .…”
Section: Discussionmentioning
confidence: 79%
“…In the previous study involving with the neural energy model, Eagleman and Pariyadath (2009) mainly used sequential stimuli and manipulated the repetition and expectation. Recently, Cai, Eagleman, and Ma (2015) presented several kinds of the stimulus sequences and measured the perceived duration of the last stimulus of the sequence. They also controlled the high-level expectation of the last stimulus by manipulating the probability of the stimulus sequence, regularity of the preceding stimuli in the sequence or whether the last stimulus broke the overlearned sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them explored the effect of numerical magnitude on time perception (e.g., Hayashi, Valli, & Carlson, 2013 ; Xuan, Zhang, He, & Chen, 2007 ). Other studies investigated how the perceived duration of a target stimulus was modulated by the other stimuli surrounding the target ( Ayhan, Revina, Bruno, & Johnston, 2012 ; Cai & Eagleman, 2015 ). In addition to these findings, we newly discovered that spatial patterns of the multiple objects on time perception.…”
Section: Discussionmentioning
confidence: 99%